2010
DOI: 10.1111/j.1600-0501.2009.01892.x
|View full text |Cite
|
Sign up to set email alerts
|

Do elderly edentulous patients with a history of periodontitis harbor periodontal pathogens?

Abstract: Periodontal pathogens may persist in the oral cavity of edentulous subjects who have had periodontal disease, even 1 year after the extraction of all teeth and in the absence of other hard surfaces in the mouth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
4
20
0
Order By: Relevance
“…Authors such as Fernandes et al. () have even suggested that periodontal pathogens can persist in the oral cavity of edentulous subjects who have suffered periodontal disease for up to 1 year after extraction of all teeth and in the absence of other hard surfaces in the mouth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors such as Fernandes et al. () have even suggested that periodontal pathogens can persist in the oral cavity of edentulous subjects who have suffered periodontal disease for up to 1 year after extraction of all teeth and in the absence of other hard surfaces in the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies (Sbordone et al 1999;De Boever & De Boever 2006;Quirynen et al 2007) have shown that periodontal pathogens can be transmitted from teeth to implants in partially edentulous patients, thus suggesting that the periodontal pockets can act as reservoirs. Authors such as Fernandes et al (2012) have even suggested that periodontal pathogens can persist in the oral cavity of edentulous subjects who have suffered periodontal disease for up to 1 year after extraction of all teeth and in the absence of other hard surfaces in the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…‘Orange complex’ pathogens, such as Fusobacterium species , and other groups of bacteria, such as Staphylococcus aureus (and even yeasts) may also contribute to chronic periodontitis . Dental implants can harbor relatively unique bacteria, but may also share the microbiota of periodontitis . Faveri et al.…”
Section: Periodontal Microbiology In Latin Americamentioning
confidence: 99%
“…There are also those who remain without any kind of prosthetic rehabilitation for long periods of time. Thus, both a CD and an edentulous oral cavity 42 can be considered microbial reservoirs that should preferably be controlled.…”
Section: 3031mentioning
confidence: 99%